Synthetic peptides for the precise transportation of proteins of interests to selectable subcellular areas - Song, Junyi; Liu, Chuanyang; Li, Baoshan; Liu, Liangcheng; Zeng, Ling; Ye, Zonghuang; Wu, Wenjian; Zhu, Lingyun; Hu, Biru (Frontiers in Bioengineering and Biotechnology, 2023)
Proteins, as gifts from nature, provide structure, sequence, and function templates for designing biomaterials. As first reported here, one group of proteins called reflectins and derived peptides were found to present distinct intracellular distribution preferences. Taking their conserved motifs and flexible linkers as Lego bricks, a series of reflectin-derivates were designed and expressed in cells. The selective intracellular localization property leaned on an RMs (canonical conserved reflectin motifs)-replication-determined manner, suggesting that these linkers and motifs were constructional fragments and ready-to-use building blocks for synthetic design and construction. A precise spatiotemporal application demo was constructed in the work by integrating RLNto2 (as one representative of a synthetic peptide derived from RfA1) into the Tet-on system to effectively transport cargo peptides into nuclei at selective time points. Further, the intracellular localization of RfA1 derivatives was spatiotemporally controllable with a CRY2/CIB1 system. At last, the functional homogeneities of either motifs or linkers were verified, which made them standardized building blocks for synthetic biology. In summary, the work provides a modularized, orthotropic, and well-characterized synthetic-peptide warehouse for precisely regulating the nucleocytoplasmic localization of proteins.